Hydrogen-Enriched Reduced Graphene Oxide with Enhanced Electrochemical Performance in Lithium Ion Batteries - Yoon, Dohyeon; Chung, Kyung Yoon; Chang, Wonyoung; Kim, Seung Min; Lee, Mi Jin; Lee, Zonghoon; Kim, Jaehoon (AMER CHEMICAL SOC, 2015)
Hydrogen-enriched reduced graphene oxide (RGO) was achieved using double-oxidized graphene oxide (GO(2)) as an anode in high-performance lithium batteries is reported. GO(2) exhibited a much lower carbon-to-oxygen ratio, lower crystallinity, higher Brunauer-Emmett-Teller surface area, higher pore volume, and higher porosity as compared to graphene oxides produced using the typical modified Hummers method (GO(1)). The two forms of GO were reduced using two different reduction methods: supercritical isopropanol (scIPA) and heat treatment. The four types of RGOs synthesized using GO(1)/GO(2) and scIPA/heat treatment exhibited significantly different chemical, morphological, and textural properties. The galvanostatic charge-discharge properties were highly dependent on the physicochemical properties of the RGOs. The scIPA-reduced GO(2) exhibited superior electrochemical performance as compared to the thermally reduced GO(1)/GO(2) and scIPA-reduced GO(1). Highly reversible capacity (1331 mAh g(-1) at 50 mA g(-1) after 100 cycles), excellent rate-performance (328 mAh g(-1) at 5 A g(-1)), and good cycling stability up to 1000 cycles even at a current density of 10 A g(-1) were observed with the scIPA-reduced GO(2) electrode. The characterization results suggested that a large amount of hydrogen-terminated groups, numerous defect sites, and large interlayer spacing have beneficial effects on the electrochemical performance of scIPA-reduced GO(2).
Keywords: SUPERCRITICAL ALCOHOLS; ANODE MATERIALS; GRAPHITE OXIDE; REVERSIBLE CAPACITY; ENERGY-STORAGE; IRREVERSIBLE CAPACITIES; ELECTRODE MATERIALS; FACILE SYNTHESIS; GREEN REDUCTION; LARGE-SCALE